Synthesis Of Piperonal Basic Material To Prepare Parfum From Lawang Oil - priatmoko, priatmoko (2009)
It has been done th synthesis o piperonal basic material to prepare parfum form lawang oil. Lawang oil contains two principle component, that are safrol and eugenol by using NaOH to separatesafrol and eugenol. Safrol that obtained was purified by using fractional distillation under diminished preasure and was obtained safrol result with 95% purity. Purified test by using GC, IR spectrometer and 1H NMR. Isomerisation of safrol was done by using t-BuOK ini dimethylsulphoxide, was refluxed along 4 hours and temperature 50°C. Isosafrol cis-trans from obtained with rendement 98,2% and 80,5% purity. Then isosafrol was oxidized by using two methode : the first by usig KMnO4, polysorbat 80 phase transfer catalyst was obstained piperonal with percentage yield 95%. The second by using K2Cr2O7 and 80-polysorbate phase transfer catalyst was obtained piperonal with percentage yield 68,8%. Purity test by using GC, IR and 1H NMR spectrometer.